3x*y-x+9y+3=13

Simple and best practice solution for 3x*y-x+9y+3=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x*y-x+9y+3=13 equation:


Simplifying
3x * y + -1x + 9y + 3 = 13

Multiply x * y
3xy + -1x + 9y + 3 = 13

Reorder the terms:
3 + -1x + 3xy + 9y = 13

Solving
3 + -1x + 3xy + 9y = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -1x + 3xy + -3 + 9y = 13 + -3

Reorder the terms:
3 + -3 + -1x + 3xy + 9y = 13 + -3

Combine like terms: 3 + -3 = 0
0 + -1x + 3xy + 9y = 13 + -3
-1x + 3xy + 9y = 13 + -3

Combine like terms: 13 + -3 = 10
-1x + 3xy + 9y = 10

Add '-9y' to each side of the equation.
-1x + 3xy + 9y + -9y = 10 + -9y

Combine like terms: 9y + -9y = 0
-1x + 3xy + 0 = 10 + -9y
-1x + 3xy = 10 + -9y

Reorder the terms:
-10 + -1x + 3xy + 9y = 10 + -9y + -10 + 9y

Reorder the terms:
-10 + -1x + 3xy + 9y = 10 + -10 + -9y + 9y

Combine like terms: 10 + -10 = 0
-10 + -1x + 3xy + 9y = 0 + -9y + 9y
-10 + -1x + 3xy + 9y = -9y + 9y

Combine like terms: -9y + 9y = 0
-10 + -1x + 3xy + 9y = 0

The solution to this equation could not be determined.

See similar equations:

| 3.1x-4=2.1x | | (2x^2+1x)+(6x+6)=0 | | ((2x^2)+1x)+(6x+6)=0 | | -3+(-3x)=18 | | 5+.50s=1s | | -5y+1(2)=5 | | -(2-8x)=3(8x-1)-16x+1 | | t(n)=-8-7(447) | | -3x-2(5y-7)=-12 | | -5+3x=3(x-6)+13 | | 180(n-2)=156 | | t(n)=14-3(447) | | 6w=8w-40 | | 1.04x/3.14=7.98 | | 19u-17u-u=20 | | 3x^3-x*y=5 | | x+6=x-4 | | ln8/ln4 | | ln8/lnr4 | | ln8/lv4 | | 9m+10-4m=-5 | | (5/9)x^2-(16/5)x-3/2=0 | | 10s-6s-3s-1=13 | | 3(8-x)-5=-6x-4+3n | | 3x-10+2x=-65 | | t(n)=-6+3(447-1) | | 4(6-9)/6= | | 8-(-4)2-5= | | 5b-b-1=7 | | 2qt=c | | 8x+3y=37 | | 3(t)=67-16t^2 |

Equations solver categories